2004
DOI: 10.1074/jbc.m313662200
|View full text |Cite
|
Sign up to set email alerts
|

Role for Mammalian Neutral Sphingomyelinase 2 in Confluence-induced Growth Arrest of MCF7 Cells

Abstract: Recently, we reported that neutral sphingomyelinase 2 (nSMase2) functions as a bona fide neutral sphingomyelinase and that overexpression of nSMase2 in MCF7 breast cancer cells caused a decrease in cell growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
136
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(146 citation statements)
references
References 67 publications
9
136
1
Order By: Relevance
“…1A). As reported previously [8], nSMase2 was localized at the plasma membrane when overexpressed in the confluent culture of MCF-7 cells (Fig. 1B).…”
Section: Plasmid Constructionsupporting
confidence: 87%
“…1A). As reported previously [8], nSMase2 was localized at the plasma membrane when overexpressed in the confluent culture of MCF-7 cells (Fig. 1B).…”
Section: Plasmid Constructionsupporting
confidence: 87%
“…1 A very recent report demonstrated that endogenous nSMase2 levels are induced upon confluence and are involved in induction of cell cycle arrest in MCF7 cells. 40,41 Furthermore, nSMase overexpression and treatment with cell-permeable ceramide analogues can induce growth arrest in a number of cells types including SK-Hep1, 6 U937 7 and HT-29. 8 Over 1000 research papers have described the induction of programmed cell death (apoptosis) by interventions that elevate the cell content of ceramide.…”
Section: Discussionmentioning
confidence: 99%
“…Scyphostatin was provided by Sankyo (Tokyo, Japan). NSMase2 (smpd3)-specific short interfering ribonucleic acid (siRNA) (AAtgttactggctggtggacc 32 ) and scrambled control (scr) siRNA (Cat. # 1022076) were from Qiagen (Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Hepatocytes were isolated from ether-anesthe-tized young (3-4 months) and aged (20-22 months) male Fisher 344 rats by in situ collagenase perfusion and cultured in culture dishes coated with 6.3 mg/ml Matrigel in Waymouth's medium supplemented with insulin (0.15 M) and penicillin/streptomycin (100 U/ml) 21 for 5 days at 37°C in 5% CO 2 . Murine nSMase2 (smpd3)-specific siRNA 32 was used to silence the endogenous NSMase-2. Transfections (100 pmol siRNA per dish) using Lipofectamine were performed on day 3 of cell culture.…”
Section: Methodsmentioning
confidence: 99%